Energy and exergy analyses of greenhouse fish drying. (29th July 2009) - Tiwari, G.N.; Das, Tribeni; Chen, C.R.; Barnwal, P.
In present study, an energy analysis has been used to predict fish surface temperature, greenhouse room air temperature and moisture evaporated during greenhouse drying of Prawn under natural and forced convection conditions. The predicted values showed fair agreements with experimental values (coefficient of correlation, r = 0.94-0.99; root mean square percent deviation, e = 2.4-10%). Analytical expression for exergy efficiency has also been developed. The exergy efficiencies under natural and forced convections were lower than corresponding energy efficiencies, as expected. However, the drying was faster in forced convection due to more moisture removal through fan.